Discriminative and predictive ability of physical performance measures in identifying fall risk among older adults - Zunaidah Abu Samah,; Devinder Kaur Ajit Singh,; Resshaya Roobini Murukesu,; Suzana Shahar,; Nor Azlin Mohd Nordin,; Mohd Azahadi Omar,; Chin, Ai-Vyrn (Penerbit Universiti Kebangsaan Malaysia, 2018)
Falls are a public health concern among older adults. There is a need to take significant measures such as screening for the risk of a fall as a means of prevention and management. A cross-sectional study was conducted to determine discriminative and predictive ability of physical performance measures in identifying the risk of fall among Malaysian community dwelling older adults. Three hundred twenty-five Malaysian community dwelling older adults aged 60 years and above (67.67+ 5.5 years) participated in this study. This study was a part of a larger longitudinal study ‘LRGS TUA’. Physiological Profile Assessment (PPA), a comprehensive tool for quantifying risk of fall was used as a standard measure of comparison to 6 Meter Gait Speed (GS), Timed Up and Go (TUG) and Walking While Talking (WWT) tests to establish discriminative and predictive ability. Participants recorded incidence of falls in a ‘falls diary’ over a span of six months. To determine the optimum cut off scores of the test identified to classify fall risk, receiver operator curves (ROC) were used and its sensitivity and specificity were calculated. A significant mean difference between fallers and non-fallers was demonstrated only with TUG test (p<0.05). TUG test cut off score in discriminating older adults at risk of fall was established at eight seconds, with a sensitivity and specificity of 83.95% and 32.4%, respectively, in this study. Eighty-four percent older adults who experienced a fall in our study were identified to be at risk of fall when screened using this TUG cut off score. Our study results suggested TUG test to be an optimal screening tool for risk of fall among community dwelling older adults.